Rough surface Au@Ag core–shell nanoparticles to fabricating high sensitivity SERS immunochromatographic sensors. Issue 1 (December 2015) - Fu, Qiangqiang; Liu, Hongwu; Wu, Ze; Liu, An; Yao, Cuize; Li, Xiuqing; Xiao, Wei; Yu, Shiting; Luo, Zhi; Tang, Yong
Abstract Immunochromatographic sensors (ICSs) are inexpensive, simple, portable, and robust, thus making ICSs commonplace in clinical diagnoses, food testing, and environmental monitoring. However, commonly used gold nanoparticles (AuNPs) ICSs have low sensitivity. Therefore, we developed highly sensitive surface enhanced Raman scattering (SERS) ICSs. To enhance the sensitivity of SERS ICSs, rough surface core–shell Au@Ag nanoparticles (RSAu@AgNPs) were prepared by coating silver on the surface of gold nanoflowers (AuNFs). Then these nanoparticles were used as SERS substrate in the SERS ICSs, after which the SERS ICSs were implemented to detect haemoglobin and heavy metal cadmium ion (Cd2+ ). The limit of detection (LOD) of the SERS ICSs for detecting haemoglobin was 8 ng/mL, and the linear range of the SERS ICSs was from 31.3 to 2000 ng/mL. The LOD of the SERS ICSs for detecting Cd2+ was 0.05 ng/mL and the linear analysis range was from 0.05 to 25 ng/mL. The cross reactivity of the SERS ICSs was studied and results showed that the SERS ICSs exhibited highly specific for detection of haemoglobin and Cd2+, respectively. The SERS ICSs were then used to detect haemoglobin (spiked in serum and in stool) and Cd2+ (spiked in tap water, river water, and soil leaching water), and the results showed high recovery. These characteristics indicated that SERS ICSs were ideal tools for clinical diagnosis and environmental pollution monitoring.